The effects of personality and cultural intelligence on international assignment effectiveness: a review - Kumar, Naresh; Che Rose, Raduan; Sri Ramalu, Subramaniam (Science Publications, 2008)
Studies on cultural intelligence (CQ) have been recently initiated dramatically in an effort to determine how they were related to positive life outcomes. While past findings showed positive correlations to various aspects of life outcomes, clear establishments of the theoretical and empirical connections of CQ on cross-cultural adjustment and job performance among expatriates was still remain elusive in the literature. Approach: The literature was explored to acknowledge the accessible relationships among CQ, cultural adjustment and job performance of expatriates. Results: This article proposes a research framework that intends to cover several gaps and weaknesses identified in the literature. The sway of personality traits on CQ and expatriate assignment effectiveness were also discussed. In offering a new research approaches, total of eight research propositions were established. Conclusions/Recommendations: This article provides an updated review of the literature on CQ. The practical implications as well as academic contributions were also presented. Thus, anticipate more empirical studies on CQ and at the same time substantiate the proposed research framework.